Online Fun Physics Experiments Untuk Meningkatkan Motivasi Belajar Siswa Sekolah Dasar Yayasan Mutiara Bunda Jember - Risse Entikaria Rachmanita; Zeni Ulma (Journal of Community Development, 2022)
Distance Learning which is currently being implemented as a result of the Covid-19 pandemic which has lasted for almost 1.5 years has caused psychological problems for students. The problems that arise include boredom due to monotonous learning, less interactive, and piling tasks. The level of education that is quite affected due to the implementation of Distance Learning is elementary school education. To overcome these problems, it is necessary to do a learning that is able to restore student motivation in learning. Mutiara Bunda Jember Foundation in collaboration with Renewable Energy Engineering lecturers at the Politeknik Negeri Jember held an interesting and interactive lesson entitled "Fun Physics Experiment". This activity was attended by 30 participants from various grade levels at the elementary school level. The results of the pretest and posttest questionnaires showed that there was an increase in participants' knowledge of light refraction, air pressure, combustion and pressure processes, heat transfer and density. In addition, after the "Fun Physics Experiment" activity, it was found that the level of interest of participants in Physics lessons increased, there were 7 participants who were very interested in Physics lessons and 23 participants were interested in Physics lessons.